# Answer to Question #22866 in Algebra for clarkie

Question #22866

Solve the equation.

3(W + 2) - 4(W +5) =0

W=

3(W + 2) - 4(W +5) =0

W=

Expert's answer

We write the equation:3(W + 2) - 4(W +5) =0

We open the brackets and multiply a definition in the brackets bythe number before brackets:

3W + 3*2 - 4W - 4*5 = 0

3W - 4W + 6 - 20 = 0

After the process of reducing similar terms, theexpression will become:

-14 - W = 0

After that we must move different terms todifferent sides:

W= -14

Answer: W = -14

We open the brackets and multiply a definition in the brackets bythe number before brackets:

3W + 3*2 - 4W - 4*5 = 0

3W - 4W + 6 - 20 = 0

After the process of reducing similar terms, theexpression will become:

-14 - W = 0

After that we must move different terms todifferent sides:

W= -14

Answer: W = -14

## Comments

## Leave a comment